ICT Complaint Management System for Pejabat Daerah dan Tanah Sabak Bernam / Norwahida Nordin - Nordin, Norwahida (2017)
This research aims is to develop the ICT Complaint Management System by applying the Shortest Job First Scheduling technique for ICT Unit in Pejabat Daerah dan Tanah Sabak Bernam. This organization provides the ICT complaint services to all staff in Pejabat Daerah dan Tanah Sabak Bernam that focus on managing all the record of complaint. In previous situations, they have difficulty to manage record of complaint. Hence, the main highlight of this research is to apply the shortest job first scheduling technique in order to solve the problem in distributing the new complaint to technician in charge. As a conclusion, all the objectives of this research are achieved. Based on the function in managing the complaint in the result was satisfying.